2009
DOI: 10.1182/blood-2009-04-211839
|View full text |Cite
|
Sign up to set email alerts
|

Naturally processed peptides spanning the HPA-1a polymorphism are efficiently generated and displayed from platelet glycoprotein by HLA-DRB3*0101–positive antigen-presenting cells

Abstract: IntroductionHuman platelet antigen (HPA)-1a and HPA-1b alloantigens are determined, respectively, by the polymorphism Leu or Pro at position 33 of the ␤ 3 chain (glycoprotein IIIa [GPIIIa]) of the platelet integrin ␣ IIb ␤ 3 . 1 Mismatch between fetal and maternal platelet antigens can lead to the production of maternal immunoglobulin G anti-HPA-1a alloantibodies that cross the placenta and cause thrombocytopenia in an HPA-1a-positive fetus. 2,3 Approximately 2% of white women are HPA-1b homozygous, and 10% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
(25 reference statements)
0
13
1
1
Order By: Relevance
“…Such structural differences may modify β3 antigenicity and possibly induce differences in the immune response to the HPA-1a and HPA-1b alleles. As far as we know, the high specific HPA-1a immunogenicity is attributed to the ability of the processed L33 β3 peptides to bind, with high affinity, the HLA-DRB3*0101 allele carried by the antigen-presenting cells [40][42]. However, although our study shows clear structural differences between the two β3 variants that may affect the antigenicity, we cannot conclude as to immunogenicity.…”
Section: Discussioncontrasting
confidence: 61%
“…Such structural differences may modify β3 antigenicity and possibly induce differences in the immune response to the HPA-1a and HPA-1b alleles. As far as we know, the high specific HPA-1a immunogenicity is attributed to the ability of the processed L33 β3 peptides to bind, with high affinity, the HLA-DRB3*0101 allele carried by the antigen-presenting cells [40][42]. However, although our study shows clear structural differences between the two β3 variants that may affect the antigenicity, we cannot conclude as to immunogenicity.…”
Section: Discussioncontrasting
confidence: 61%
“…This strong association suggests that CD4 T-cell activation by the DRA/DRB3*01:01 molecule is a determining event in the immune response against HPA-1a. In support of this notion, it has been shown that integrin β3-derived peptides with Leu33 (HPA-1a peptide), but not with Pro33, bind well to the DRA/DRB3*01:01 molecule and thus can be presented by antigen-presenting cells 30,31. Also, HPA-1a-specific DRA/DRB3*01:01-restricted CD4 T cells have been isolated from women who have had a child affected by FNAIT 32,33.…”
Section: Pathogenesismentioning
confidence: 97%
“…The second frequent antigen causing NAIT is HPA‐5b (10%‐15% of NAIT cases), while all the rest cause NAIT very rarely 11 . Only 10% of HPA‐1b–homozygous women with an HPA‐1a–positive fetus develop anti‐HPA‐1a alloantibodies during pregnancy 12 . Maternal responsiveness to HPA‐1a shows strong association with DRB*0101 allele encoding human histocompatibility leukocyte antigen DR52a.…”
Section: Data Of the Hpasmentioning
confidence: 99%